Anxiety Stadium Of Women's Handball Athletes Of The Contingent Of Bengkulu Province In Preparation For The Match At Pon Xxi Aceh-Sumut - Ilahi, Bogy Restu; Raibowo, Septian (UNIB Press, 2024)
This study aims to determine the anxiety stadium of female handball athletes from the Bengkulu Province contingent in preparation for the match at PON XXI Aceh-Sumut. This research uses qualitative research with an emphasis on case studies using data collection techniques in the form of interviews, questionnaires and documentation. The subjects of this research were 2 coaches, 2 assistant coaches, and 19 athletes. The object of this research was the anxiety stadium of female handball athletes from the Bengkulu Province contingent in preparation for the match at PON XXI Aceh-Sumut. The research instruments used were interview guidelines, questionnaires and photo guidelines. Based on validation results from experts, 93% and 94% were obtained in the